Volunteers awareness level among student ACIS in UiTM Puncak Alam to support philanthropy / Farhatul Hasanah Kamal - Kamal, Farhatul Hasanah (Academy of Contemporary Islamic Studies (ACIS), 2018)
Philanthropy is an area of deep concern improving the capabilities of a community. It is acapable activity giving value to human development especially youth. The study of this exercise has examined the spirit of volunteerism among students of Academy Contemporary Islamic Studies (ACIS) in University Teknologi MARA Cawangan Selangor Kampus Puncak Alam. A total of ACIS students are 110 were involved in the study which is 55 from Halal management course and 55 from Muamalat course. Meanwhile, as a problem is the awareness and understanding of public regarding this philanthropy concept. The question arise about what is the best step to make sure more students involve in volunteer activity. It is due to lack of time and awareness among the students that make them involve in volunteer activity. Moreover, the primary objective of this study is to measure the level of awareness of the volunteers to support philanthropy. It uses the method of quantitative method which distributed survey to measure about the awareness level of them to support philanthropy. Meanwhile the qualitative method is to give some additional strength to the research. In conclusion, it will hope that this research will give benefits to the students for the betterment of awareness to help the needy to educate about it.